How high-performance practitioners think and intervene to change technique - Vecchione, J.; Bundon, A.; Madill, C.; Hodges, N. (Psychology of Sport and Exercise, 2025)
OBJECTIVE Changing technique, whereby a permanent strategy is adopted to improve performance or reduce injury risk, is a common goal among sport practitioners in high performance sports. However, there is little information about how technique change is done in practice and whether any evidence-based methods or frameworks are applied. Our aim was to explore individual and team-sport practitioner experiences concerning the process and types of methods adopted for technique change, across a range of practitioner groups and sports.